Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1155/2022/5035369
|View full text |Cite|
|
Sign up to set email alerts
|

Research on Virtual Interactive Animation Design System Based on Deep Learning

Abstract: With the rapid development of computer network technology, the advantages of virtual reality technology in the field of instant messaging are becoming more and more significant. Virtual reality technology plays an important role in communication networks, including enhanced resource utilization, device redundancy, immersion, interactivity, conceptualization, and holography. In this paper, we use the basic theory of Restricted Boltzmann Machine to establish a semisupervised spatio-temporal feature model through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The proposed VRAID-BPINN-AOA method is implemented in MATLAB and evaluated under some metrics. Obtained results of HAD-TSV-ITF-CZNN technique are analysed with existing techniques likes VI-AD-RBM [21],GDL-VALD-GAN [22], HID-LVIR-CNN [23]correspondingly.…”
Section: Results With Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed VRAID-BPINN-AOA method is implemented in MATLAB and evaluated under some metrics. Obtained results of HAD-TSV-ITF-CZNN technique are analysed with existing techniques likes VI-AD-RBM [21],GDL-VALD-GAN [22], HID-LVIR-CNN [23]correspondingly.…”
Section: Results With Discussionmentioning
confidence: 99%
“…Liu [21] have presented Studying Design Systems for Virtual Interactive Animation with a Foundation in Deep Learning Using the problem of style recognition in animation capture data, the fundamentals of the Restricted Boltzmann Machine are applied to create a semi-supervised spatio-temporal feature model. When the top model's parameters remain unchanged and only the bottom model requires retraining, the model is considered well parallelized.…”
Section: Literature Surveymentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%